The FOUND questionnaire: identifying stable traits associated with success in remote operations—an exploratory study - Cesari, Valentina; Cipriani, Enrico; Papini, Giorgia; Piarulli, Andrea; Gemignani, Angelo; Menicucci, Danilo (Frontiers in Systems Neuroscience, 2025)
IntroductionThis study introduces the FOUndatioNal trait-BaseD Characterization (FOUND) questionnaire, specifically developed to assess stable characteristics of perceptual, cognitive, and emotional domains associated with effective performance in mediated settings.Materials and methodsItems were derived from interviews with professionals in remote technology fields (e.g., robotic surgeons, drone pilots, crane operators) and grouped into four domains: cognitive-behavioral, socio-emotional, functional-organic, and value-based. Items, rated on a 4-point Likert scale, were designed to reflect stable traits. A panel of nine experts evaluated content validity; items with a CVI > 0.78 and a mean relevance ≥3 were retained, resulting in a 26-item scale. The factorial structure of FOUND was validated in a sample of 300 Italian participants, with convergent validity assessed, and participants were subsequently categorized into high and low procedural skill professions for known-groups comparisons (Study 1). Additionally, a separate sample of 34 remote operators (Study 2) was included to further evaluate known-groups validity.ResultsExploratory and confirmatory factor analyses yielded a final 22-item structure, identifying four factors: Perception and Action, Empathic Attitude, Stress Management, and Group-Oriented Values. Convergent validity analysis using questionnaires that assess personality and stable characteristics (Five Facet Mindfulness Questionnaire-15, Big Five Inventory-10) did not yield significant correlations, indicating that the FOUND questionnaire may provide independent information. Known-groups validity was assessed by comparing scores between professions requiring high and low procedural skills identified in the 300 participants, revealing higher scores in Perception and Action, Empathic Attitude, and Stress Management for the first group (Study 1). Comparing remote operators (i.e., drone pilots) with the general population showed that remote operators scored higher in Perception and Action and Group-Oriented Values but lower in Stress Management, highlighting distinctive characteristics of individuals engaged in remote operations (Study 2).ConclusionThe FOUND assesses perceptual, motor, cognitive, and socio-emotional constructs associated with performance in mediated and remote operations. It allows evaluation of stable traits and performance-related attitudes in contexts such as robotic surgery, telemedicine, education, and emergency response. By identifying these traits, the questionnaire can inform the design of personalized interventions and training programs tailored to individual characteristics, enhancing effectiveness in mediated environments.